Membangun Server Portable untuk VoIP dan Web Server di Linux Ubuntu - Dwiny Meidelfi -; Hidra Amnur -; Afrima Deki - (Jurnal Ilmiah Poli Rekayasa, 2018)
Server is a computer that serves a particular task in the network which can be used by other computers. The server damage will cause some losses in various parties who use the server services. Losses can be in the form of financial or others. The server damage can also be caused by natural disasters, such as earthquakes, floods, landslides and others. Therefore, it is necessary to create a portable server for VoIP and web server. VoIP servers are built by using asterisk as well as using the zoiper app and 3CX Phone to run VoIP.  Meanwhile, the web server is created by using sentora panel. sentora panel is used because it has an installed packet like apache, php, mysql, phpmyadmin and other supporting software, hence it does not need to install it one by one. This portable server can be taken anywhere and can also be used in various PC or Laptop. So when the natural disaster occurs, the server stay safe, and ready to use.